Brazilian Federal Institutes and Canadian Colleges: Sharing Experiences Internationally - Schiedeck Soares de Souza, Claudia (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2020)
The Brazilian Federal Network of VET Institutes was created in 2008 to address the demand for Higher Education’s rapid growth. Since the establishment of Science Without Borders in 2011, the Federal Institutes have been developing international strategies for strengthening their internationalization process. However, there has been little research about the theme in Brazil. This article highlights the cooperation between Canada and Brazil that enhanced the Federal Institutes’ internationalization process. The findings presented in this article are part of the research results on the Brazilian Federal Institutes’ internationalization model, which used Situational Analysis as a methodological tool and pointed to the A Thousand Women project as the first significant international experience in these institutions. The data analyzed supports the claim that Canada became a significant reference for the Brazilian Federal Institutes and helped them build their internationalization process concretely and collaboratively.